Designing Anterior Hair Line in Male Pattern Baldness: Innovative Method A Study Of 431 Cases - Dr. Seema Garg, Dr. Anil Kumar Garg (International Journal of Innovative Research in Medical Science, 2017)
Introduction - Anterior hair line (AHL) separates face from scalp. Evidence suggests our perception of physical beauty is based on how closely the features of one’s face reflect phi (the golden ratio) in their proportions. Meaning, all faces perceived to be beautiful, each different from the other are united in their adherence to the golden ratio. By that extension, it must certainly be possible to use a mathematical parameter to design AHL in all faces. Method - this is method of designing anterior hair line in patients of male pattern baldness. We need simple a flexible measuring tape and skin marker. A reference point “A” (glabella) is taken in between eyebrows. Mark points E and E’ near lateral canthus on either side 8 cm horizontally away from point A. Mid frontal point, (point B) is marked 8 (+/- 1 cm) cm from point A in mid vertical plane. A Fronto-Temporal point, (points C) is marked by intersection of two points. One is 8 cm away in horizontal plane from point B and another is 8 cm away in vertical plane from point E. The Temporal Peak Points (D and D’) are marked on line joining fronto temporal peak point (E, E’) to lateral canthal points (C C’). This line makes anterior border of temporal triangle. The temporal peak point is taken slightly more than half way towards lateral canthus usually 5 cm away from fronto temporal point. Observation- Author has done a study of 431 cases. All cases were of MPA. The average distance of mid frontal point from glabella was 7.9 cm. the patient satisfaction was 94.7%, few wanted lowering of hair line. Conclusion - Based on study of various hair line, animation model of conversion of anterior hair line on 3D face to 2D, Golden ratio and Leonardo da Vinci concept that a common figure of approximately 8 cm plus minus one centimetre can give design of anterior hair line in cases of male pattern baldness.